2016
DOI: 10.3390/toxins8070223
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between TNF and BmooMP-Alpha-I, a Zinc Metalloprotease Derived from Bothrops moojeni Snake Venom, Promotes Direct Proteolysis of This Cytokine: Molecular Modeling and Docking at a Glance

Abstract: Tumor necrosis factor (TNF) is a major cytokine in inflammatory processes and its deregulation plays a pivotal role in several diseases. Here, we report that a zinc metalloprotease extracted from Bothrops moojeni venom (BmooMP-alpha-I) inhibits TNF directly by promoting its degradation. This inhibition was demonstrated by both in vitro and in vivo assays, using known TLR ligands. These findings are supported by molecular docking results, which reveal interaction between BmooMP-alpha-I and TNF. The major cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
7
0
2
Order By: Relevance
“…In our previous study, we investigated the role of BmooMP-alpha-I as a biological product able to hydrolyze the TNF cytokine, based mainly on in vitro experiments, as well as on modeling and docking approaches [18]. We concluded that this metalloprotease could be used to modulate of the inflammatory response, but this application would require further investigation, particularly when tested to treat inflammatory disorders involving the TNF cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we investigated the role of BmooMP-alpha-I as a biological product able to hydrolyze the TNF cytokine, based mainly on in vitro experiments, as well as on modeling and docking approaches [18]. We concluded that this metalloprotease could be used to modulate of the inflammatory response, but this application would require further investigation, particularly when tested to treat inflammatory disorders involving the TNF cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in the present study, we advanced in the process to characterize this metalloprotease as a modulator of the inflammatory response, by using an in vivo experimental design already applied in our group to assess an experimental inflammatory bowel disease [20]. Therefore, when compared with our previous studies [18, 20], it is necessary to emphasize that the present work investigated for the first time the use of the BmooMP-alpha-I metalloprotease to treat DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these venom proteins are fully trapped inside the polymer nanomatrix at the instant of nanoparticle cross-linking. Furthermore, that Bothrops venom has negatively charged peptides [ 9 , 61 ] can also explain the high loading efficiency. These results demonstrate the substantial ability of the optimized nanoparticle formulation to carry negatively charged proteins, maintaining colloidal stability, which is not common for particle-encapsulated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the venom is responsible for causing inflammation in several systems and models and triggers specific pathways and processes that can be a determinant of the OCs differentiation process [ 3 , 38 , 39 ]. Classically, this process depends on various inflammatory factors and needs a strictly balanced system, as changes in the membrane, receptors, and degradation of compounds can lead to several responses that influence differentiation [ 2 , 40 , 41 ]. B. moojeni venom’s effect is well known in human snakebite processes [ 42 , 43 , 44 ], which have not yet been reported in the OCs model, thus being totally exclusive and relevant data.…”
Section: Discussionmentioning
confidence: 99%